HADITH SCIENCE AND ITS EDUCATIONAL SIGNIFICANCE - Oqboyeva , Gulnoza; Norboyeva , Mohigul (Journal of Pedagogical and Philological Research, 2026)
This topic discusses the coverage of educational issues in the most ancient written monuments and the educational significance of Hadith science. In ancient written sources, ideas that call for spiritual maturity, the acquisition of knowledge, and the formation of manners and ethics hold a primary place. Particularly in the historical monuments that are considered our people’s spiritual heritage, the issues of educating the young generation and raising them to be patriotic, hardworking, and well-mannered individuals have gained great importance. Hadith science is one of the main sources of Islamic teaching, encompassing the words, deeds, and recommendations of our Prophet Muhammad (PBUH). Hadiths call a person to high virtues such as honesty, patience, kindness, respect for parents, and the pursuit of knowledge. Therefore, Hadith science is of great importance not only from a religious perspective but also from pedagogical and educational viewpoints. Through this topic, the role of ancient written monuments and Hadiths in the upbringing of the young generation is extensively highlighted.